Are library electronic resources providing adequate support for research? A case study of a federal university in the United Arab Emirates. (12th August 2019) - Ho, Lilly Hoi Sze
Abstract : Purpose: Middle Eastern universities have recently been included in international rankings, driving a shift in priorities from teaching to research. However, research-centric collection assessments are rarely applied in the region. The Library and Learning Commons of Zayed University has recently completed the first phase of collection assessment for this transition. This study aims to provide an overview of how electronic resources adequacy was measured, and correlations between utilization of resources and research output were determined. A systematic approach is presented to assess electronic resources impact and to investigate and demonstrate the Library's support of research output in local research and the scholarly environment. Design/methodology/approach: Journal article publications from 2009 to 2016 with at least one Zayed University affiliated author were collected from Scopus, the abstract and citation database operated by Elsevier BV. Sources used within these articles were analyzed. COUNTER usage statistics of three indicators (searches, sessions and full-text downloads) were collected from the most used electronic resources in the Library to define the correlation between usage and research activities in the university during the assessment period. Findings: The change in university direction toward research is apparent in the data since Fall 2014. Since then, faculty publication output grew rapidly and was positively correlated with library resources use. Sessions and searches displayed a strong positive relationship with research output while the correlation with full-text downloads was moderate. This was true for individual colleges as well as for the university as a whole, supporting the assumption that library utilization is highly correlated with the growth of research productivity. Practical implications: Results of this assessment were used to justify the budget allocation of Zayed University Library for supporting research and improve the focus of collection development to better meet researchers' needs. The most important outcomes were to provide evidence-based information to Library management for strategic planning and evaluation of their changing role in the digital age. Originality/value: The systematic approach described has enabled Zayed University library to assess the relevance of its resources to its changed focus toward research, both for the university as a whole and among the more research-productive colleges. This initial approach may be useful for other libraries going through a similar transition, particularly within the region.